Flourishing in later life - Momtaz, Yadollah Abolfathi; Tengku Abdul Hamid, Tengku Aizan; Haron, Sharifah Azizah; Bagat, Mohamad Fazdillah (Elsevier, 2016)
Objective: Flourishing is a relatively new concept in positive psychology that considers hedonic and eudaimonic aspects of well-being. The current study aims to identify the prevalence and socio-demographic and health factors associated with flourishing among older Malaysians. Methods: The sample for this study consisting of 2202 community-dwelling older Malaysians was obtained from a national survey entitled "Identifying Psychosocial and Identifying Economic Risk Factor of Cognitive Impairment among Elderly", conducted from May 2013 to April 2014. Data analyses were conducted using the IBM SPSS Version 22.0 and AMOS Version 22.0. Results: The average age of the respondents was 69.05 (SD = 6.24) years. Descriptive results showed that 50.1% of the respondents were flourishing in life, 36.3% were languishing, 8.4% were struggling, and 5.2% were floundering in life. The results of Multiple logistic regression analysis revealed that gender, employment status, level of education, having living children, and chronic medical conditions are significantly associated with flourishing. However, age, marital status, living alone, and economic status did not have much impact on flourishing. Conclusion: To the best of our knowledge, the current study is one of the first studies that conceptualizes and assesses flourishing among older adults in Malaysia. The findings from the present study make important contributions to the existing literature on well-being. It is suggested that health and social care professionals working with older adults adopt a comprehensive approach to identify and propel non-flourishing people toward flourishing in life.